Physical, Chemical, and Organoleptic Characteristics of Smoked Skipjack Tuna (Katsuwonus pelamis) in Kendari City - Isamu, Kobajashi T.; Purnomo, Hari; Yuwono, Sudarminto S. (Fakultas Teknologi Pertanian Universitas Brawijaya, 2012)
The objective of this research was to determine the physical, chemical, and organoleptic characteristics of smoked skipjack tuna fish in Kendari. This research evaluated smoke meterials used by producers, colour (L,* a*, b*), texture, aw, proximate (moisture, protein, fat and ash) and organoleptic (colour, flavor, texture and aroma) characteristics of smoked skipjack tuna. Tis research used descriptive method with three replications. The results showed differences of color (L*, a*, b*), texture, aw, moisture, protein, fat and ash of smoked skipjack tuna produced by different producers. Organoleptic analysis indicated that differences were resulted by different smoke methods. Keywords: skipjack tuna, smoking process, smoked fish